2019
DOI: 10.21315/mjms2019.26.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Work-Related Musculoskeletal Disorders and Their Associated Factors in Nurses: A Cross-Sectional Study in Iran

Abstract: Background Work-related musculoskeletal disorders (WMSDs) in nursing are regarded as an important factor for creating tension since they may often cause discontent, leave profession, and provide incorrect services to their clients. The present study aimed to determine WMSDs and their related factors among the nursing staff in university hospitals affiliated to Shiraz University of Medical Sciences (SUMS). Methods In the present descriptive cross-sectional study, 300 nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 33 publications
(35 reference statements)
3
16
1
1
Order By: Relevance
“…Awkward postures assumed during work activities including inappropriate and poor lifting techniques were constantly connected with back pain experiences in the present study. This aspect has also been expressed in other studies (Heidari et al, 2019;Mwilila and Frantz, 2008;Geiger-Brown et al, 2004) and is worsened by lack of equipment and poor work settings. Repetitive postures and movements may be a cause of cumulative pressure to the musculoskeletal system causing back pain among nurses.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Awkward postures assumed during work activities including inappropriate and poor lifting techniques were constantly connected with back pain experiences in the present study. This aspect has also been expressed in other studies (Heidari et al, 2019;Mwilila and Frantz, 2008;Geiger-Brown et al, 2004) and is worsened by lack of equipment and poor work settings. Repetitive postures and movements may be a cause of cumulative pressure to the musculoskeletal system causing back pain among nurses.…”
Section: Discussionsupporting
confidence: 52%
“…Nursing activities assume lots of physical care that involves movement and patient support which sometimes may have unpredictable events due to weight and poor gripping which may lead to injuries for the nurse (Alnaami et al, 2019;Heidari et al, 2019). These outcomes may suggest that there is a mismatch between job activities performed by nurses to meet work demands and their physical abilities or the need for more advanced technologies and/or equipment to assist with the load.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MSDs in various positions of coal miners with severe burnout is much higher than that of coal miners affected by job burnout to a lesser degree, suggesting that there is a certain relationship between job burnout and MSDs in this population and confirming that job burnout is a risk factor for MSDs. Psychosocial factors have been reported to have a noticeable effect on MSDs [37,38], with adverse psychosocial factors shown to change human behavior and lead to the occurrence of MSDs [39] via a two-way feedback between psychosocial factors and MSDs [40]. Studies outside China have also shown that psychological factors and physical load simultaneously influence the prevalence of MSDs [41].…”
Section: Discussionmentioning
confidence: 99%
“…These tasks are performed on an unstable platform and generally in a cold climate, leading to greater tension in standing workers. Therefore, workers on fishing vessels, similar to other professionals, are exposed to several risk factors that contribute to the development of work-related musculoskeletal disorders (WMSDs) [8,9].…”
Section: Introductionmentioning
confidence: 99%